PELATIHAN PENGGUNAAN APLIKASI SPSS UNTUK MENUNJANG TUGAS AKHIR MAHASISWA - Setia Sandi A, Arif; Nugroho Triwibowo, Deny; Bagus Bambang Sumantri, Raden; Cipta Sigitta Haryono, Rito (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
The training activity on the usage of the Statistical Analysis SPSS Application (Statistical Package for the Social Sciences) was conducted to enhance students' skills in analyzing data to support the completion of their final assignments. This article elucidates the methods and benefits of this training, tailored to suit the students' material needs, aiding them in finalizing their assignments. These sessions were conducted through a series of workshops accommodating students from diverse scientific backgrounds. The outcomes of these activities provided insights into the competency and proficiency regarding SPSS application use in enhancing students' statistical analysis skills. The implications of these activities could serve as a guide for higher education institutions in designing training programs that support the development of student’s academic skills in data analysis, thereby bolstering their final assignment requirements. The results of these activities demonstrate a significant improvement in students' understanding of statistical concepts, SPSS utilization, and the necessary data analysis skills required for final assignment research.